Domestic violence (KDRT) in the dynamics of the rights and obligations of husband and wife from an Islamic law perspective - Danial, Ahmad; Halim, Abdul; Ramadhan, Riski (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
This study examines the dynamics of domestic violence (DV) in the context of Muslim families with a focus on the understanding and implementation of the rights and obligations of husbands and wives according to Islamic family law. The approach used is qualitative with case studies. This study involved in-depth interviews with victims, perpetrators, and religious figures and Islamic legal experts, as well as observations of the mediation process and resolution of domestic conflicts. Data analysis was carried out through data reduction, display, and verification to ensure the validity and reliability of the findings. The results of the study indicate that inequality in the fulfillment of the rights and obligations of husbands and wives is the main factor triggering domestic violence, and the implementation of Islamic family law within a positive legal framework can strengthen protection for victims. These findings provide new insights into preventing and handling domestic violence through an approach based on Islamic values and enrich the perspective of Islamic family law in the context of legal plurality in Indonesia. Keywords: Domestic Violence, Rights and Obligations of Husband and Wife, Islamic Law